Optimum Design of Structures for Earthquake Induced Loading by Genetic Algorithm Using Wavelet Transform (Advances in Applied Mathematics and Mechanics, 2010)
Optimum design of structures is achieved by genetic algorithm. Theevolutionary algorithm is employed to design structures. The methodimproves the computing efficiency of the large-scale optimizationproblems and enhances the global convergence of the design process.The loads are considered as earthquake loads. A time historyanalysis is carried out for the dynamic analysis. To decrease thecomputational work, a wavelet transform is used by which the numberof points in the earthquake record is reduced. A reverse wavelettransform is also employed to reconstruct the functions underconsideration in the time domain. A number of space structures aredesigned for minimum weight and the results are compared with exactdynamic analysis.